1998
DOI: 10.1104/pp.117.3.841
|View full text |Cite
|
Sign up to set email alerts
|

The Never ripe Mutant Provides Evidence That Tumor-Induced Ethylene Controls the Morphogenesis ofAgrobacterium tumefaciens-Induced Crown Galls on Tomato Stems1,2

Abstract: We confirm the hypothesis that Agrobacterium tumefaciensinduced galls produce ethylene that controls vessel differentiation in the host stem of tomato (Lycopersicon esculentum Mill.). Using an ethylene-insensitive mutant, Never ripe (Nr), and its isogenic wild-type parent we show that infection by A. tumefaciens results in high rates of ethylene evolution from the developing crown galls. Ethylene evolution from isolated internodes carrying galls was up to 50-fold greater than from isolated internodes of contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 32 publications
3
55
0
1
Order By: Relevance
“…Interestingly, ethylene treatment of various plant species causes xylem occlusion, which leads to the wilt phenotype of vascular diseases (Van der Molen et al, 1983;Perez-Donoso et al, 2007). In addition, it was shown that ethylene produced by galls of Agrobacterium-infected tomato plants decreases the diameter of xylem vessels in the stem adjacent to the tumor (Aloni et al, 1998). In light of these observations, it is tempting to speculate that ethylene emission by Cmminfected tissues may contribute to the development of wilt symptoms by affecting physical properties of xylem vessels in the host plant.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ethylene treatment of various plant species causes xylem occlusion, which leads to the wilt phenotype of vascular diseases (Van der Molen et al, 1983;Perez-Donoso et al, 2007). In addition, it was shown that ethylene produced by galls of Agrobacterium-infected tomato plants decreases the diameter of xylem vessels in the stem adjacent to the tumor (Aloni et al, 1998). In light of these observations, it is tempting to speculate that ethylene emission by Cmminfected tissues may contribute to the development of wilt symptoms by affecting physical properties of xylem vessels in the host plant.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that auxin and ET control vascular development in plants as well as in tumors (Aloni et al, 1998, and it is well known that high auxin levels induce ET emission. Besides their action in pathogen defense during initiation of infection with agrobacteria, this may imply an additional role for these phytohormones in regulating vascular development at later stages of tumor development.…”
Section: Auxin and Et Are Involved In The Initiation Of Infection Witmentioning
confidence: 99%
“…JA and ET accumulate in response to pathogen infection or herbivore damage, resulting in the activation of distinct sets of pathogenesis-related genes (PR). It has been reported that along with auxin and cytokinin (Weiler and Schroeder, 1987;Zambryski et al, 1989;Malsy et al, 1992), the phytohormone ET is a limiting factor of crown gall morphogenesis because ET deficiency or insensitivity leads to inhibition of tumor growth (Aloni et al, 1998;Wachter et al, 2003). SAmediated defense responses provide protection from biotrophic fungi, oomycetes, and bacteria, including Erysiphe orontii, Peronospora parasitica, and Pseudomonas syringae.…”
Section: Introductionmentioning
confidence: 99%
“…From tumors of castor bean (Ricinus communis) it was proposed that the synthesis of auxin and cytokinin promotes an increased production of ethylene. Communication between the tumor and the host plant might well be provided by this gaseous factor, which in turn triggers synthesis of high ABA content in leaves of the host plant (Aloni et al, 1998;Wächter et al, 1999;Veselov et al, 2003). Since Arabidopsis tumors produce increased levels of the ethylene precursor ACC and develop very close to rosette leaves, ethylene diffusion seems very likely.…”
Section: Aba Induces Drought Adaptations and Regulates Water Flow Intmentioning
confidence: 99%